Geophysical Mapping of Aquifer Potential Zones Using Hydraulic Parameters in Lokoja and Environs, North-Central, Nigeria - Omali, O. A.; Arogundade, J. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This research is aimed at delineating the groundwater potential in Lokoja and environs using Dar Zarrouk parameters. The study area is part of the Basement Complex of South-western Nigeria and the Lokoja sub-basin of the middle Niger sedimentary basin, on area coverage of about 400km2. Thirty-five (35) vertical electric soundings (VES) using Schlumberger array method with the aid of ABEM Signal Averaging System (SAS) Terrameter were used for the data acquisition. The result of the interpretation shows four geo-electric layers. The resistivity soundings results revealed that about 4 curve types were identiﬁed in the study area namely AA, HA, A and H type with the lithologic layers varying from 3 to 4 and consisting of varying resistivity and thicknesses across each VES point. The geo-electric sections revealed that the major aquifer systems in the study area are weathered basement and weathered/fractured basement. The longitudinal conductance computed that range from 0.00904951 to 0.7814713 Ω-1indicates that the aquifers in the area have poor to moderate protective capacity whereas transverse resistance that range from 24.5841 to 7290.15Ω indicates very low groundwater development class. Hydraulic conductivity with a range of 0.36757M/day to 56.86754M/day and transmissivity values with a range of 4.4548 to 917.273M2 /day indicate very low to moderate aquifer capable of sustaining moderate communities.